CAHAYA, ALAT OPTIK, DAN GANGGUAN PADA MATA - Elfida dhiu; Yolita Frederika Ndana; Ainun Jariyah; Maria Garsela Gidha (Jurnal Bionatural, 2025)
Vision is a precious sense, involving the intricate interaction between light, eye structure, and optical technology. Light is the main source of information, an electromagnetic wave with a visible spectrum wavelength of 400–700 nm. The human eye is a natural optical organ, where light passes through the cornea (contributing 2/3 of the refractive power) and crystalline lens, then focused onto the retina, which converts it into electrical signals. Various vision disorders, such as myopia (nearsightedness) affecting over 15% of Indonesian school-age population, are increasing due to modern lifestyles. Optical tools, such as spectacles (concave lenses for myopia, convex for hypermetropia) and contact lenses, are used for refractive correction. Advanced technology includes LASIK surgery (reshaping the cornea with a laser) and Optical Coherence Tomography (OCT) for early diagnosis of retinal disorders. Eye disorder prevention includes the 20-20-20 Rule, carotenoid and omega-3 nutrition, and protection from UV and blue light. This article provides a deep understanding of the physical properties of light, eye anatomy, optical instruments, and eye disorders, along with practical tips for maintaining eye health.